Analisis Pelanggaran Etika dalam Praktik Akuntansi: Studi Kasus Manipulasi Laporan Keuangan pada eFishery - Nur Agustin, Merlin; Khoirunaya, Shahnaz; Tirta Aprilia, Tania; Lidtwin Titirloloby, Emiliana; Saridawati, Saridawati (Politeknik Negeri Jakarta, 2025)
This research aims to examine violations of the ethics of the accounting profession in the case of alleged manipulation of financial statements at the start-up company eFishery. This case surfaced after reports that eFishery allegedly prepared two different versions of financial statements for internal and external purposes. The method used in this research is descriptive qualitative with a case study approach, where data is obtained through non-participant observation and literature study of news articles, investigation documents, and academic references related to accounting professional ethics. The results of the study show that the actions taken by eFishery are contrary to the principles of accounting ethics, especially the principles of integrity, objectivity, and transparency. These violations were allegedly triggered by the pressure of business growth, investor demands, and weak internal controls. The impact of these violations is very serious, including reputational damage, loss of stakeholder trust, and potential legal sanctions. This study emphasizes the importance of applying professional ethics in accounting practice to maintain business credibility and sustainability, especially in the growing startup ecosystem in Indonesia. Keywords: Professional ethics; accounting; financial statement manipulation